P140 OBSERVATIONAL STUDY WITH ONE YEAR FOLLOW-UP ON ROBOTIC ASSISTED RETRO-RECTUS VENTRAL HERNIA REPAIR (RTARUP) WITH A SELF-FIXATING MESH. (25th November 2021) - Muysoms, Filip; Dewulf, Maxime; Nachtergaele, Femke; Pletinckx, Pieter
Abstract: Aim: Laparoscopic retro-rectus ventral hernia repair avoids the need for intra-peritoneal mesh placement and penetrating mesh fixation. The robotic platform facilitates the execution of this technique. Material and Methods: From a prospective consecutive single center database all patients that underwent a robotic assisted trans-abdominal retro-rectus ventral hernia repair (rTARUP) via lateral single docking using a self-fixating mesh (ProGrip) were identified. Results: Between September 2016 and December 2019, 203 patients were included. There were 89 (44%) umbilical hernias, 34 (17%) epigastric hernias and 80 (39%) incisional midline hernias. Patients had a mean BMI of 29 kg/m 2 . The mean hernia diameter was 3.2 cm and mainly located in zone M2-M3-M4 of the EHS classification. The mean operative time was 85 min (SD: 33 min) and all except one were clean operations. The self-fixating mesh was mostly 15 cm wide with a variable length between 15 and 30 cm. No intra-operative complications or conversions to open surgery. Intra-hospital complications were seen in 12 patients (6%) and one patient needed a reoperation for bleeding. The operation was performed in day care in 37% of patients and hospital stay was less than 24 hours in 80%. There were 6 readmissions within 30 days of surgery (3%). At 12 months clinical follow-up 3 patients were documented with a recurrence and 2 underwent an laparoscopic intra-peritoneal hernia repair. Due to COVID-19 restrictions a clinical follow-up was only possible in 73 % of patients and needs updating. Conclusions: This case series reports favorable early clinical outcome of an innovative retro-rectus repair using the robotic platform.